Comparative Analysis of Coral Cover Percentage and Species Diversity in Karanrang Island, Balang Lompo Island, Badi Island, and Lumu-Lumu Island Using the Underwater Photo Transect (UPT) Method - Gracela; Nita Rukminasari; Jamaluddin Fitrah Alam; Sri Wahyuni Rahim (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
This study assessed live coral cover and coral genus diversity across Karanrang Island, Balang Lompo Island, Badi Island, and Lumu-Lumu Island. Data collection was conducted at 12 observation stations (depth ±5 m) using the Underwater Photo Transect (UPT) method in April 2025. Photo analysis with CPCe 4.1 software was used to calculate the percentage of live coral cover, while the diversity index was calculated using the Shannon-Wiener formula (H’). The findings revealed that Badi Island exhibited the highest live coral cover (32.31–45.03%), whereas Lumu-Lumu Island demonstrated the lowest condition (10.60–24.97%). The highest diversity index was recorded on Balang Lompo Island (H' = 2.53) and the lowest on Karanrang Island (H' = 0.83). Badi Island is predominantly composed of Porites sp. and Acropora sp., suggesting ecosystem stability and a high potential for regeneration, while Karanrang and Balang Lompo Islands display moderate conditions with a prevalence of adaptive massive corals. These results show variations in coral cover and diversity between islands due to differences in environmental pressures and the ecological characteristics specific. These findings emphasize the need for location-based management to maintain the ecological functions and restoration potential of coral reefs ecosystem in the Spermonde Islands.